Sociodemographic profile, diagnoses and nursing care in post-COVID-19 patients in a Brazilian university hospital - Evelyn Klein dos Santos; Fernando Riegel; Jhonatan Tyson Barros Azevedo; Maria da Graça Oliveira Crossetti; Margarita Ana Rubin Unicovsky; Jussara Gue Martini; Paula Bresolin; Andrea Aparecida Gonçalves Nes (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to analyze the sociodemographic profile, diagnoses and nursing care of post-COVID-19 patients admitted to a university hospital in southern Brazil. Methods: a retrospective cohort study. The sample consisted of 1,467 medical records, from January 2020 to January 2021. Results: from the analyzed medical records, the most prevalent profiles, respectively, included: males (52.9%); white (81.1%); with Impaired Physiological Balance Syndrome* Nursing Diagnosis (77.3%); nursing care implementing aerosol precautions (94.5%); implementing droplet precautions (93.4%); checking vital signs (91.9%); applying standard disinfectant to equipment and surfaces (89.6%). Conclusions: the analysis of the sociodemographic profile, diagnoses and nursing care of patients in this study may contribute to implementing the Nursing Process in the coronavirus pandemic context.